FLUCTUACION EN LA DENSIDAD DE POBLACION DEL PULGON VERDE DE LA ALFALFA ACYRTHOSIPHON PISUM HARRIS Y DE SU PARASITOIDE APHIDIUS SMITHI SHARMA Y SUBBA RAO EN CHAPINGO MEX - VERA GRAZIANO, JORGE; SOSA MOSS, CARLOS; CARRILLO, JOSE LUIS (Centro de Economía Agrícola, Colegio de Posgraduados, 1972)
si
AGRO
Keywords: FLUCTUACION, DENSIDAD, POBLACION, PULGON VERDE, ALFALFA, ACYRTHOSIPHON PISUM, HARRIS, PARASITOIDE APHIDIUS SMITHI SHARMA, SUBBA RAO, CHAPINGO, MEX; CIENCIAS AGRARIAS; FITOPATOLOGIA; PARASITOIDES